(untitled) (Bangladesh Journal of Plant Taxonomy, 2023)
In this research paper, a newly identified plant species of the genus Abutilon Mill., namely Abutilon jafrii F. Naseer, A. Noor & A. Rahman, is described and illustrated for the first time in the province of Sindh, Detailed morphological descriptions of the species along with the micro-morphological examinations of scanning electron microscopy (SEM) for the mericarps, seeds and pollens are presented. Additionally, Macro morphological characteristics including photographs of the plant habit with flowers, fruits, seeds and mericarps are provided. Through gross macro-morphological and micro-morphological investigations such as plant height, leaves texture and colour, pedicel of fruits and flowers, flowers diameter, sepal’s size in flowers and fruits, number of seeds per mericarp, pollen tectum exhibit significant differences in characters, which indicate that, it is a distinct species. Bangladesh J. Plant Taxon. 30(1): 43-51, 2023 (June)